2018
DOI: 10.1002/mp.12830
|View full text |Cite
|
Sign up to set email alerts
|

Changes in prostate orientation due to removal of a Foley catheter

Abstract: Removing a Foley catheter can cause large prostate rotations. There does not appear to be a clear dosimetric benefit to obtaining the CT scan with a Foley catheter to define the urethra given the changes in urethral position from removing the Foley catheter. If urethral sparing is desired without the use of a Foley, utilization of an MRI to define the urethra may be necessary, or a pseudo-urethral planning organ at risk volume (PRV) may be used to limit dosimetric hot spots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Other studies investigating the impact of prostate rotations have tended to focus on the dosimetric changes to the PTV and when we look at this data it does appear that these rotations have an effect on the dose coverage of the prostate [27][28][29] , with rotations in the pitch axis generally being the primary component. 30 However, the CTV-PTV margin is meant to take motions such as these, as well as other factors including delineation error, into account in order to ensure adequate coverage of the CTV. For delineation, the use of a single observer for all contouring with a known variation of approximately 1-2mm on MRI will reduce the impact of this error, and the control for real time translational error should also reduce uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies investigating the impact of prostate rotations have tended to focus on the dosimetric changes to the PTV and when we look at this data it does appear that these rotations have an effect on the dose coverage of the prostate [27][28][29] , with rotations in the pitch axis generally being the primary component. 30 However, the CTV-PTV margin is meant to take motions such as these, as well as other factors including delineation error, into account in order to ensure adequate coverage of the CTV. For delineation, the use of a single observer for all contouring with a known variation of approximately 1-2mm on MRI will reduce the impact of this error, and the control for real time translational error should also reduce uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results may have suggested that the Foley catheter in the urethra itself has changed the actual position of the urethra at rest. A recent study by Litzenberg et al showed that removing the Foley catheter from the urethra caused significant prostate rotation [12].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, urethra-sparing radiotherapy (USRT) using IG-IMRT, in which the dose to the prostatic urethra (Fig. 1) is intentionally reduced, is attracting attention and reported as an attempt to minimize GU toxicities furthermore [912]. For example, Shimizu et al have proposed USRT for prostate cancer [10] using fluoroscopic real-time tracking technology, called real-time tumor-tracking radiotherapy, and three fiducial gold markers with the accuracy of ±1–2 mm [1318].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this method must be done prior to each treatment, is invasive and can lead to infection. Additionally, the catheter can also rotate and deform the urethra, resulting in potential organ misalignment during each treatment delivery [ 8 , 9 , 10 ]. As a result, some physicians choose to contour the prostatic urethra on the planning CT based on prior experience and knowledge.…”
Section: Introductionmentioning
confidence: 99%